Waris dan Wasiat dalam Pertentangan Ayat Al-Qur'an - Syuhada' Syuhada' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Human entrusted property as ruler of the world. So entrusted to death, the property back into the hands of the Lord automatically. Because God does not accept the property, then given to families designated by the rules of revelation. Setting the rules of media ownership property with inheritance and probate. In the verses of inheritance and will appear in which contradict each other to remove the provision. While it is believed that there are verses in the Qur’an which have been removed so that it does not work, including the verses of inheritance and wills. By placing verse as wills and testaments muh?kamah verse as a compromise with the h?adîth mukhas?s?is not make erase status and erased in the verses of the Koran. Elimination naskh supported by state law to decrease gradually in terms of the condition of society. With inheritance and probate law as set out in the passage suggests that nas?s? inheritance and probate law are interrelated and complementary.